2021
DOI: 10.3390/ma14226748
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Effect on the Structure and Optical Properties of CBD-ZnS Thin Films for Windscreen Coating

Abstract: Zinc sulfide (ZnS) thin films were prepared and synthesized by the chemical bath deposition (CBD) technique on microscopic glass substrates using stoichiometric amounts of the precursor materials (ZnSO4·7H2O, NH4OH, and CS(NH2)2). Structural, morphological, compositional, and optical characterization of the films were studied. The obtained thin films were found to exhibit polycrystalline possessions. The effect of annealing temperature on the crystallographic structure and optical bandgap of ZnS thin films wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…CBD-deposited ZnS films have been reported by many researchers. In the literature (see Table 3 ), the following chemical reagents were employed to prepare ZnS: zinc acetate [ 88 , 89 ], zinc acetate dihydrate [ 11 , 75 , 90 , 91 , 92 , 93 , 94 , 95 ], zinc chloride [ 11 , 76 , 90 , 96 , 97 , 98 ], zinc nitrate [ 99 ], zinc nitrate hexahydrate [ 90 ], zinc sulfate [ 11 , 77 , 78 , 85 , 100 , 101 , 102 , 103 ], and zinc sulfate heptahydrate [ 21 , 58 , 69 , 90 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ] as a source of Zn 2+ ions; sodium sulfide […”
Section: Synthesis Of Zns Thin Films Using a Chemical Bath Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…CBD-deposited ZnS films have been reported by many researchers. In the literature (see Table 3 ), the following chemical reagents were employed to prepare ZnS: zinc acetate [ 88 , 89 ], zinc acetate dihydrate [ 11 , 75 , 90 , 91 , 92 , 93 , 94 , 95 ], zinc chloride [ 11 , 76 , 90 , 96 , 97 , 98 ], zinc nitrate [ 99 ], zinc nitrate hexahydrate [ 90 ], zinc sulfate [ 11 , 77 , 78 , 85 , 100 , 101 , 102 , 103 ], and zinc sulfate heptahydrate [ 21 , 58 , 69 , 90 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ] as a source of Zn 2+ ions; sodium sulfide […”
Section: Synthesis Of Zns Thin Films Using a Chemical Bath Depositionmentioning
confidence: 99%
“…The pH regulator of an alkaline solution was adjusted by adding ammonia ( ) [ 18 , 69 , 75 , 85 , 96 , 100 ] and potassium hydroxide (KOH) [ 76 ], and the acidic solution was adjusted by hydrochloric acid (HCl) [ 90 ]. The sulfur sources utilized included sodium sulfide ( [ 94 ], thioacetamide ( ) [ 88 , 90 ], and thiourea ( ) [ 11 , 21 , 58 , 69 , 75 , 76 , 77 , 78 , 85 , 89 , 92 , 93 , 95 , 96 , 97 , 98 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]. The zinc sources utilized included zinc acetate ( [ 88 , 89 ], zinc acetate d...…”
Section: Synthesis Of Zns Thin Films Using a Chemical Bath Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohammed et al [ 5 ] investigated ZnS thin layers prepared by deposition in a chemical bath. They investigated the structural properties of films deposited and annealed at a temperature of 300 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammed et al [5] investigated ZnS thin layers prepared by deposition in a chemical bath. They investigated the structural properties of films deposited and annealed at a temperature of 300 • C. This research found that relatively small grains were randomly formed and the deposited film had a heterogeneous surface with some cracks.…”
Section: Introductionmentioning
confidence: 99%